2005
DOI: 10.1007/s10450-005-5607-2
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Adsorption of Pesticides onto Activated Carbon Fibers

Abstract: The adsorption equilibria of pesticides and metabolites (atrazine, deethylatrazine, deisopropylatrazine and simazine) are studied onto activated carbon fibers -ACF-with a broad pore size distribution (32% mesopore volume, 68% micropore volume). Mono-and multi-component isotherms have been determined for low concentrations, from 0.23 × 10 −6 to 9.52 × 10 −6 mol L −1 . Single solute isotherms, modeled by Freundlich and Langmuir models, tend to prove the influence of the adsorbate's solubility in the adsorption c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 35 publications
(36 reference statements)
1
19
0
Order By: Relevance
“…Comparing the correlation coefficients of the three equations indicates that the equilibrium experimental data for HAC and HAC N 2 are best fitted by the Langmuir-Freundlich equation, while atrazine adsorption onto HAC HNO 3 and HAC NH 3 is described by the Langmuir equation. Langmuir monolayer adsorption was also reported for atrazine adsorption onto activated carbon prepared from rubber tire waste (Gupta et al 2011) and commercial activated carbon fibers (Faur et al 2005). However, in most reports the sorption isotherms of atrazine for various adsorbents were best fitted by the Freundlich model (Kovaios et al 2006;Tang et al 2012;Labeau et al 1999).…”
Section: Equilibrium Adsorption Of Atrazinementioning
confidence: 95%
“…Comparing the correlation coefficients of the three equations indicates that the equilibrium experimental data for HAC and HAC N 2 are best fitted by the Langmuir-Freundlich equation, while atrazine adsorption onto HAC HNO 3 and HAC NH 3 is described by the Langmuir equation. Langmuir monolayer adsorption was also reported for atrazine adsorption onto activated carbon prepared from rubber tire waste (Gupta et al 2011) and commercial activated carbon fibers (Faur et al 2005). However, in most reports the sorption isotherms of atrazine for various adsorbents were best fitted by the Freundlich model (Kovaios et al 2006;Tang et al 2012;Labeau et al 1999).…”
Section: Equilibrium Adsorption Of Atrazinementioning
confidence: 95%
“…In the case of a binary or multi-components system, adsorption capacities of each individual pesticide were noted proportionally less with another, indicating the existence of competition for available sites, with non-equal adversary to the heterogeneity of carbon surface. Accordingly, pesticide with the greatest ionic potential saturation value may effectively occupy most of the active sites hindering further adsorption of other pesticides by possessing a lower affinity [51].…”
Section: Classmentioning
confidence: 99%
“…However, single component isotherm data revealed that PIPC showed good biosorption capacity towards all three reactive dyes. Therefore direct sites competition may be the predominant competition mechanism [22], with all reactive dyes competing with each other in occupying the same amine group.…”
Section: Competitive Biosorption and Modelingmentioning
confidence: 99%